Development of Statistics Learning Worksheets Based on Realistic Mathematics Education for Junior High School Students - Noer, Miftah Sakina; Hanifah, Hanifah; Susanta, Agus; Susanto, Edi (FKIP Universitas Lampung, 2022)
The purpose of this study was to develop valid, practical, and effective statistics learning worksheets based on realistic mathematics for eighth grader of junior high school. This development research uses a 4D development model with stages: definition, design, development, and deployment. The subjects of this research trial were the students of class VIII SMP Negeri 7 Bengkulu City, as many as 27 people. The research instrument consisted of product validity sheets, practicality sheets, and student learning outcomes tests. The data analysis consisted of validity analysis using Aiken's V index, rater agreement test, and N-gain test. This study resulted in realistic mathematics education-based student worksheet for statistical material for class VIII SMPN that met the following criteria: (1) Valid with an average Aiken's V index score of 0.86 in the high category and the results of the agreement test between raters with an intraclass correlation coefficient score of 0.99 categories. Very good. (2) Very practical in terms of the average practicality score of students of 81.51%. (3) Effective from the N-gain score of 0.72 high categories with classical completeness reaching 81.48%. Keywords: students worksheet, development research, realistic mathematics education DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1395-1408